Government Social Assistance and Economic Diversification on The Welfare of Coastal Communities in Poverty Alleviation in Palopo City - ferdian, Arif; Ramli , Alimuddin; Syamjaya, Syamjaya; Darmawati, Darmawati (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
The aim of this article is to analyse and assess the impact of social assistance, economic diversification in poverty alleviation through public welfare. This type of research is exploratory quantitative. By using the PLS-SEM analysis technique in the SMARTPLS application, the analysis technique used is PLS Alogarithm, Boostripping, and Blindfolding. researchers investigate the impact between exogenous latent variables on endogenous latent variables. The results showed that there was an influence of exogenous latent variables on endogenous latent variables. It is known that the P-value is smaller than the value of 0.50 and the T-statistic value is greater than the T-Table value of 1.663 so that all hypotheses are accepted. The magnitude of the effect of government social assistance and economic diversification on poverty alleviation is 50.2% while the effect of government social assistance, economic diversification and poverty alleviation on community health is 60.7%. It can be concluded that social assistance, economic diversification plays a role in helping coastal communities in Palopo city to overcome poverty.